2007
DOI: 10.1002/app.26435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of liquefied wood residues from different liquefaction conditions

Abstract: ABSTRACT:The amount of wood residue is used as a measurement of the extent of wood liquefaction. Characterization of the residue from wood liquefaction provides a new approach to understand some fundamental aspects of the liquefaction reaction. Residues were characterized by wet chemical analyses, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The Klason lignin content of the residues decreased, while the holocellulose and a-cellulose contents i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 31 publications
5
50
0
1
Order By: Relevance
“…[34,35] The more intense peak at 1 215 cm À1 attributed to C-C, C-O, and C5 5O stretch indicated that more phenol-lignin complex in the residues from HCl catalyzed bark liquefaction than the residues from H 2 SO 4 catalyzed bark liquefaction, which was also consistent with the results that the residues from HCl catalyzed bark liquefaction had a higher lignin content. The peak at 1 168 cm À1 due to the C-H in-plane deformation in guaiacyl with a stronger intensity in the residues from HCl catalyzed bark liquefaction also supported that H 2 SO 4 can more effectively liquefy the lignin than HCl.…”
Section: Unliquefied Residues From Bark Liquefactionsupporting
confidence: 89%
See 1 more Smart Citation
“…[34,35] The more intense peak at 1 215 cm À1 attributed to C-C, C-O, and C5 5O stretch indicated that more phenol-lignin complex in the residues from HCl catalyzed bark liquefaction than the residues from H 2 SO 4 catalyzed bark liquefaction, which was also consistent with the results that the residues from HCl catalyzed bark liquefaction had a higher lignin content. The peak at 1 168 cm À1 due to the C-H in-plane deformation in guaiacyl with a stronger intensity in the residues from HCl catalyzed bark liquefaction also supported that H 2 SO 4 can more effectively liquefy the lignin than HCl.…”
Section: Unliquefied Residues From Bark Liquefactionsupporting
confidence: 89%
“…Lignin was reported as the most reactive components in phenol liquefaction and had the tendency to undergo secondary condensation reactions, while cellulose was reported as the most resistant components in phenol liquefaction. [3,9,10,[23][24][25]34] Early View Publication; these are NOT the final page numbers, use DOI for citation !! efficient to give a higher yield of liquefied bark than HCl catalyzed bark liquefaction.…”
Section: Unliquefied Residues From Bark Liquefactionmentioning
confidence: 99%
“…The resins and their fractions do not absorb at these frequencies. Therefore, the polycondensation reaction probably proceeds by addition across the C=C double bond and condensation across the aldehyde group [19][20]. Figure 1 shows the Differential Scanning Calorimetry (DSC) thermogram for phenolic oligomers.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks associated with lignin (1510 cm -1 , 1610 cm -1 , 1460 cm -1 and 1220 cm -1 ) have also shown marked reduction in the wood residues particularly obtained with 1:2 and 1:3 liquid ratios. Pan et al (2007) has also reported disappearance of peak at 1735 cm -1 , attributed to the ester carbonyl group in xylan, in the FTIR spectra of the residues from liquefied wood. They observed reduction in the Klason lignin content and increase holocellulose and α-cellulose contents as the phenol to wood ratio (P/W) increased.…”
Section: Ftir Characterizationmentioning
confidence: 90%